2016
DOI: 10.1021/acs.orglett.6b03264
|View full text |Cite
|
Sign up to set email alerts
|

Dimericbiscognienyne A: A Meroterpenoid Dimer from Biscogniauxia sp. with New Skeleton and Its Activity

Abstract: Dimericbiscognienyne A (1), an unusual diisoprenyl-cyclohexene-type meroterpenoid dimer, was isolated from Biscogniauxia sp. together with three new monomeric diisoprenyl-cyclohexene-type meroterpenoids (2-4) and one new isoprenyl-benzoic acid-type meroterpenoid (5). All structures were determined by extensive NMR spectroscopic methods, quantum chemical calculations, chemical derivatization, and X-ray crystallography. The formation of 1 is related to a unique intermolecular redox coupling Diels-Alder adduct re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…The key NOESY correlations (Table S1 ) between H-5′/H-9′ and H 3 -13′/H 3 -14′ indicated that the configuration of the double bond of ∆ 2′ as Z . Furthermore, the 13 C NMR data of guignardianone unit in 1 were quite similar to those of ( S, Z )-guignardianone C ( 4 ) 14 , 16 , which confirmed the above deduction. In addition, the alkaline hydrolysis of 1 give a major reaction product ( 1a ) that was identified as (4 S , 6 R , 9 S , 10 R , 14 R )−17-hydroxylated guignardone A ( 7 ) 18 by HPLC, NMR data, and electronic circular dichroism (ECD) comparisons (Figures S1 – S3 ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The key NOESY correlations (Table S1 ) between H-5′/H-9′ and H 3 -13′/H 3 -14′ indicated that the configuration of the double bond of ∆ 2′ as Z . Furthermore, the 13 C NMR data of guignardianone unit in 1 were quite similar to those of ( S, Z )-guignardianone C ( 4 ) 14 , 16 , which confirmed the above deduction. In addition, the alkaline hydrolysis of 1 give a major reaction product ( 1a ) that was identified as (4 S , 6 R , 9 S , 10 R , 14 R )−17-hydroxylated guignardone A ( 7 ) 18 by HPLC, NMR data, and electronic circular dichroism (ECD) comparisons (Figures S1 – S3 ).…”
Section: Resultssupporting
confidence: 74%
“…Among them, the five aromatic protons indicated the existence of a mono-substituted benzene ring moiety in 1 . Combined with the DEPT-135 spectrum, 31 signals were observed in the 13 C NMR spectrum, which can be assigned to eight sp 2 quaternary carbons (including one ketone carbonyl and two ester carbons), six sp 2 methine carbons, one sp 2 methylene carbon, three sp 3 O -quaternary carbons, four sp 3 methine carbons (including one O -methine carbon), six sp 3 methylene carbons (including two O -methylene carbons), and three methyl carbons. Based on the analysis of 1 H− 1 H COSY experiment, four subunits (C-4—C-5, C-8—C-9—C-14—C-13—C-12, C-5′—C-6′—C-7′—C-8′—C-9′, and C-13′—C-12′—C-14′) were revealed as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous explorations for bioactive secondary metabolites from fungi 23 , 24 , we identified the endolichenic fungus Nodulisporium sp. (no.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Zhao et al [20] isolated five new compounds from secondary metabolites of Biscogniauxia sp., including the isolation of one new skeleton diisoprenyl-cyclohexene-type of meroterpenoid dimer—dimericbiscognienyne A 2 (Figure 2). In their anti-Alzheimer’s disease (AD) fly assay study, dimericbiscognienyne A showed short-term memory enhancement activities in AD flies [20].…”
Section: Epoxidesmentioning
confidence: 99%